The Positive Brain – Resting State Functional Connectivity in Highly Vital and Flourishing Individuals - Goldbeck, Florens; Haipt, Alina; Rosenbaum, David; Rohe, Tim; Fallgatter, Andreas J.; Hautzinger, Martin; Ehlis, Ann-Christine (Frontiers in Human Neuroscience, 2019)
The World Health Organization has defined health as “complete physical, mental and social well-being and not merely the absence of disease or infirmity” (Preamble to the Constitution, 1948). An increasing number of studies have therefore started to investigate “the good life”. However, the underlying variation in brain activity has rarely been examined. The goal of this study was to assess differences in resting state functional connectivity (RSFC) between regular healthy individuals and healthy individuals with a high occurrence of flourishing and subjective vitality. Together, flourishing, a broad measure of psycho-social functioning and subjective vitality, an organismic marker of subjective well-being comprise the phenomenological opposite of a major depressive disorder. Out of a group of 43 participants, 20 high-flourishing (highFl) and 18 high-vital (highSV) individuals underwent a 7-minute resting state period, where cortical activity in posterior brain areas was assessed using functional near-infrared spectroscopy (fNIRS). Network-based statistics (NBS) of FC yielded significantly different FC patterns for the highFl and highSV individuals compared to their healthy comparison group. The networks converged at areas of the posterior default mode network and differed in hub nodes in the left middle temporal/fusiform gyrus (flourishing) and the left primary/secondary somatosensory cortex (subjective vitality). The attained networks are discussed with regard to recent neuroscientific findings for other well-being measures and potential mechanisms of action based on social information processing and body-related self-perception.